2018
DOI: 10.1186/s13750-018-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

What specific plant traits support ecosystem services such as pollination, bio-control and water quality protection in temperate climates? A systematic map

Abstract: Background Agricultural intensification has contributed to increased diffuse source pollution within water catchments, reduced heterogeneity within the landscape and caused major declines in farmland wildlife. This decrease in biodiversity has been shown to decrease vital ecosystem services such as pollination, biological pest control (bio-control) and water quality protection. The morphological traits of plant species, such as floral display size and leaf area, provide support to these service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The primary purpose of extracting this meta-data was to aid future study validity assessments and synthesis of studies on sub-topics of interest identified from our systematic map exercise. Study validity assessments were based on a modified list of variables used by Haddaway et al [30] and combined with topic specific quality measures used by Cresswell et al [31]. Terms including 'yes' , 'partially' , 'not at all' , or 'unclear' were applied to each study based on study design (i.e., type of comparator), sample-selection methods, and other sources of bias as outlined below.…”
Section: Study Validity Assessment Study Validity Assessmentmentioning
confidence: 99%
“…The primary purpose of extracting this meta-data was to aid future study validity assessments and synthesis of studies on sub-topics of interest identified from our systematic map exercise. Study validity assessments were based on a modified list of variables used by Haddaway et al [30] and combined with topic specific quality measures used by Cresswell et al [31]. Terms including 'yes' , 'partially' , 'not at all' , or 'unclear' were applied to each study based on study design (i.e., type of comparator), sample-selection methods, and other sources of bias as outlined below.…”
Section: Study Validity Assessment Study Validity Assessmentmentioning
confidence: 99%
“…One way to optimise multiple benefits from field margins at the field and landscapes scale could therefore be to adjust management practices locally according to purpose. Cresswell et al [58] used systematic mapping to identify which plant traits deliver different ecosystem services to help inform future plant community design of vegetative strips.…”
Section: Multipurpose Vegetated Strips and Conflicting Objectivesmentioning
confidence: 99%
“…From a total of 11,705 from the initial search, 56 articles met all the relevant criteria to be included for data extraction. Data extracted from the systematic map report (Cresswell et al, ), on the identified plant traits and their corresponding ecosystem service, are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Plant traits and related ecosystem services investigated in the literature. (Data adapted from Cresswell et al ()…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation